A study of the Lexical Approach on Identification and Learning Collocations among EFL Students in private Universities in Erbil City - Arsalan Abdulla Faqe; Nada Jabbar Abbas (Zanco Journal of Humanity Sciences)
The current study seeks to investigate the role of Lexical Approach on the Learning and Identification of Collocations among EFL learners enrolled in Erbil City’s private universities. The main objective of the current research entails the need to offer insight on the basic language acquisition field which carries significant weight as regards the capacity of EFL learners to attain effective communication in the English language. The study population for this research brings on board learners and educators in Erbil-based private universities and it included 40 participants who were 30 EFL learners alongside ten educators. Consequently, the study responds to the research questions through participant questionnaire responses which were analyzed through SPSS quantitative means. Through the analysis, the findings hinted that a majority of the learners could recognize a lexical item. Based on the findings of this study, it is recommended that English educators need to organize multiple exchange programs for EFL learners to enable them access opportunities for increased interaction with native speakers of the English language as well as enhancing immersion chances. Thus, the current study views that English language educators have a role of ensuring exchange programs for EFL learners to enable them access opportunities for interaction with native English speakers for increased immersion.